PELAKSANAAN UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL TERHADAP PENDAFTARAN SERTIFIKAT HALAL PADA PRODUK MAKANAN - Melissa Aulia Hosanna; Susanti Adi Nugroho (Jurnal Hukum Adigama, 2018)
Food is one of the most necessary needs of humans to survive so that everyone is expected to pay more attention to the food products that will be consumed.Indonesia is a country with a predominantly Muslim population. In the teachings of Islam there are orders to consume halal food and prohibition to consume illegitimate food. Halal product is a product that qualifies halal according to Islamic syariat from its substance, its process and its storage and presentation. This study aims to determine the implementation of law number 33 of 2014 on the guarantee of halal products on the registration of halal certificates on food products and what are the constraints faced in registering halal certificates.The guarantee of consumer protection against the circulation of halal labeled food products is already guaranteed according to the prevailing laws and regulations and the products labeled official halal have provided legal certainty to the halal nature of the product itself which can be seen from the authority given by the government to MUI and BPJPH.